Sources of Stress in Teaching Physical Education in Senior High Schools in the Cape Coast Metropolis - Bonney, Albert Kofi; Stephen Sorkpor, Richmond; Forson, Emily Araba (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to conduct quantitative descriptive survey to find out sources of stress regarding the teaching of the subject Physical Education in Senior High Schools in the Cape Coast Metropolis of Ghana. Data was collected from 30 respondents who are Physical Education teachers from 10 second cycle schools. Questionnaires were used to collect data for the study. It was found out that sources of stress in the teaching of Physical Education in Senior High Schools in Cape Coast include workload, role ambiguity, lack and insufficient equipment and facilities. The study recommended that periodic workshops on sources of stress are organized for second cycle Physical Education teachers